Sobreposição de transformações e desafios: experiências de mães de adolescentes na pandemia da COVID-19 - Alem Filho, Fabio (Universidade Federal de São Carlos, 2022)
In the tangle of social relations, adolescence is processed and adolescents emerge. Adolescence is part of the individual and family life cycle, encompasses particular development processes towards identity assumptions and life projects, during which transformations are experienced at different levels. The COVID-19 pandemic imposed changes in social dynamics, among which is the tendency for adolescents to stay at home. This study proposed to explore the perception of parents about adolescence in the context of the pandemic. The proposed objective was to elucidate meanings and behaviors of parents in supporting adolescents in the COVID-19 pandemic. This is a qualitative study with a descriptive and exploratory approach, supported by Symbolic Interactionism and thematic Content Analysis. Semi-structured interviews were developed with mothers of adolescents between the 1st half of 2021 and the 2nd half of 2022, enabling and encouraging a space for speech to share perceptions and afflictions regarding the growth of children in a scenario of uncertainty. From the interviews, three categories were created: interaction with the adolescent in transformation; relations in the face of the pandemic and its consequences; adaptations, revelations and concerns arising from living together. This study provided a space for family discussion that enabled reflections on topics not always addressed in family life and that can have positive consequences for raising and living with adolescents. we believe that this research can contribute to deepening the available knowledge about families, adolescents and the pandemic, in order to support health professionals in the care and monitoring of families and adolescents, as it brings important discussions about family life during the process of social isolation and favors the construction of knowledge to support these individuals who, many times, are not assisted with quality due to lack of understanding and knowledge on the part of professionals.
Overlapping transformations and challenges: experiences of mothers of adolescents in the COVID-19 pandemic
Keywords: Adolescência; Família; Pandemia; COVID-19; Pesquisa qualitativa; Adolescence; Family; Pandemic; Qualitative research; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA